Modeling antibody dynamics following herpes zoster indicates that higher varicella-zoster virus viremia generates more VZV-specific antibodies - Besbassi, Hajar; Garcia-Fogeda, Irene; Quinlivan, Mark; Breuer, Judy; Abrams, Steven; Hens, Niel; Ogunjimi, Benson; Beutels, Philippe (Frontiers in Immunology, 2023)
Studying antibody dynamics following (re-)exposure to infection, and/or vaccination, is challenging but critical for a better understanding of fundamental immunological processes and consequently, vaccine development and health policy research. Here, we adopted a nonlinear mixed modeling approach based on ordinary differential equations (ODE) to characterize varicella-zoster virus-specific antibody dynamics during and after clinical herpes zoster. Our ODEs models convert underlying immunological processes into mathematical formulations, allowing for testable data analysis. In order to cope with inter- and intra-individual variability, mixed models include population-averaged parameters (fixed effects) and individual-specific parameters (random effects). We explored the use of various ODE-based nonlinear mixed models to describe longitudinally collected markers of immunological response in 60 herpes zoster patients. Starting from a general formulation of such models, we study different plausible processes underlying observed antibody titer concentrations over time, including various individual-specific parameters. Among the converged models, the best fitting and most parsimonious model implies that once VZV reactivation is clinically apparent (i.e., HZ can be diagnosed), short-living and long-living antibody-secreting cells (SASC and LASC, respectively) will not expand anymore. For more homogeneity and a better understanding of the population's characteristics, a covariate model was investigated and built, in which the influence of age and viral load was explored. Our model-based approach indicates that more circulating VZV stimulates SASC to produce more VZV-specific antibodies and, unexpectedly, older individuals seem to have more persistent SASC than younger ones. These results provide unique and essential information to improve both our understanding of VZV antibody dynamics, and projections of the potential impact of vaccines.